A Study on the Development of Strategic Tools in Study Orientation Skills towards Achieving Academic Excellence - Mohd Ghani, Awang; Suriya Kumar, Sinnadurai (Academy Publisher, 2011)
The purpose of this research is: to measure: the study orientation skills: and to provide remedial tools in correcting respondents’ study orientation skills faults. The research also measures the relationship between study orientation skills and the academic performance among first year students of University Malaysia PAHANG. The measurement of study orientation skills is done by innovating a website based on a survey of study habits and attitudes questionnaire (SSHA); http://portal.ump.edu.my/survey. The students’ study orientation skills are analyzed and sorted into three groups of achievement; the higher achiever, normal achiever and lower achiever. The treatment tools comprise of the treatment website; http://portal.ump.edu.my, a textbook (Study Orientation Skills in Action, Ghani format of note-taking, DVD on the study orientation skills and lecture on study orientations skills aspects. The assessment on the academic performance is based on grade point average (GPA) scores of UMP undergraduates from their first semester and second semester results. 59 respondents are randomly selected from two groups of undergraduate students from the Faculty of Computer Science & Information Technology and from the Faculty of Civil Engineering & Natural Resources. The research uses Quasi-experimental design with a pre-test and post-test by comparing both group samples. The finding has shown that the study orientation skills (SOS) website was able to measure SOS effectively among the respondents in the two groups. There is a significant difference in SOS and academic performance between pre-test and post test scores of the respondents. The results also show that there is a correlation between SOS and GPA scores in pre-test and post-test within and between each group.